The Use of Biologically Converted Agricultural Byproducts in Chicken Nutrition - Ababor, Sebsib; Tamiru, Metekia; Alkhtib, Ashraf; Wamatu, Jane; Kuyu, Chala; Teka, Tilahun; Lemlem Arega Terefe, Lemlem Arega Terefe; Burton, Emily (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This article aims to uncover the current knowledge on using bioconverted agricultural byproducts in the chicken diet and the impact of these byproducts on performance, product quality, and health status. Agricultural and agro-industrial activities generate thousands of tons of byproducts. Converting these agricultural byproducts into valuable entities would be an environmentally friendly, sustainable, and viable part of byproduct management. Upon recycling to make new products, the process contributes to socio-economic value and maintaining environmental health and paves the way for realizing energy security and a circular economy. The current paper identifies that solid-state fermentation has attracted more research attention than other fermentation counterparts because it requires minimal moisture, good oxygen availability, cheap media, low wastewater generation, low cost, a low processing scheme, low energy demand, and high productivity. This paper illustrates the role of proteolytic and lignin-degrading enzymes present in bacteria and fungi in the bioconversion process of complex polymers into smaller molecules of amino acids and simple sugar with a profound improvement in the palatability and bioavailability of agricultural products. In addition, the paper gives more detailed insights into using bioconverted agricultural products in chickens to improve performance, product quality, gut microbiota and morphology, and chicken welfare. In conclusion, the bioconversion of agricultural byproducts is an encouraging endeavor that should be supported by governments, research centers, universities, and non-governmental entities to improve the productivity of animal source foods by ensuring environmental sustainability and expanding food security efforts for national development.